Facilitating and Supporting Multistakeholder Scaling Hubs in West and Central Africa - Ndindeng, S.A.; Nwilene, F.; Bah, S.; Twine, E.E.; Tang, E.; Savadogo, E.; Tchatcha, D.; Ndungu, J.; Kittika, M.; Faye, F.; Dembele, A.; Konan, G. (2025)
Under AoW2 Activity 2.1.2.1, AfricaRice facilitated and supported multistakeholder scaling hubs as operational, country-anchored delivery platforms to accelerate the scaling of rice-based and diversified food-system innovations in five West and Central African countries. This report is a consolidated rewrite grounded in empirical data generated through TAAT-II, Seeds4Liberia, and HealthyDiets4Africa (HD4A). Evidence from these three initiatives shows that scaling hubs enabled the coordination of seed and planting material systems, post-harvest and processing technologies, youth and women enterprises, digital platforms, and nutrition-sensitive demand pathways within unified delivery ecosystems. Across the five countries, hub-based implementation contributed to measurable results, including large-scale seed delivery, establishment of certified seed clusters, creation of youth-led enterprises, commercial food production and sales, and mobilization of institutional demand and financing. Taken together, the data demonstrate that multistakeholder scaling hubs—when operational, institutionally embedded, and supported by digital and enterprise systems—are an effective mechanism for translating CGIAR innovations into sustained, system-level impact